2014
DOI: 10.1021/jf501528s
|View full text |Cite
|
Sign up to set email alerts
|

Inverse Relationships between Biomarkers and Beef Tenderness According to Contractile and Metabolic Properties of the Muscle

Abstract: Previous proteomic analyses established a list of proteins biomarkers of beef tenderness. The present study quantified the relative abundance of 21 of these proteins by dot-blot technique in the Longissimus thoracis and Semitendinosus muscles of 71 young bulls from three breeds: Aberdeen Angus (AA), Limousin (LI), and Blond d'Aquitaine (BA). For both muscles overall tenderness was estimated by sensory analysis; shear force was measured with a Warner-Bratzler instrument, and an index combining sensory and mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
126
1
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 137 publications
(176 citation statements)
references
References 36 publications
16
126
1
6
Order By: Relevance
“…On the contrary, some proteins representative of fast glycolytic properties (Activities of metabolic enzymes such as Lactate Dehydrogenase and PhosphoFructoKinase, Myosin heavy chain-I, α-enolase 1, β-enolase 3) appears more abundant. This is in agreement with previous results indicating that in French beef breeds, the LT is more tender when it contains lower abundance of fast glycolytic proteins (Picard et al, 2014).…”
Section: Resultssupporting
confidence: 94%
“…On the contrary, some proteins representative of fast glycolytic properties (Activities of metabolic enzymes such as Lactate Dehydrogenase and PhosphoFructoKinase, Myosin heavy chain-I, α-enolase 1, β-enolase 3) appears more abundant. This is in agreement with previous results indicating that in French beef breeds, the LT is more tender when it contains lower abundance of fast glycolytic proteins (Picard et al, 2014).…”
Section: Resultssupporting
confidence: 94%
“…Yambayamba and Price (1991) suggested that a decrease in the energy intake of the animal leads to muscle with more oxidative fibres than glycolytic fibres. The studies of Picard et al (2007Picard et al ( , 2014 demonstrated that in French beef breeds, bulls that had the more tender LT also had a lower proportion of IIX fibres. The results of the present study are in accordance with these data as LT from the 0.6 group contained a numerically lower proportion of IIX fibres and was rated more tender.…”
Section: Discussionmentioning
confidence: 99%
“…Многие из этих данных были получены с использованием 2DGE and MS [11]. Было высказано предположение, что сре-ди 21 изученного белка, небольшой белок теплового шока Hsp70-1B может служить биомаркером недоста-точной нежности говядины [12]. Другие более ранние исследования говорят о том, что такие биомаркеры как изоформы тяжелой цепи миозина или цепь В лактатдегидрогеназы, по всей вероятности, являются специфичными для мышцы или породы.…”
Section: Proteomics In Research On Muscle Biochemistryunclassified
“…Many of these data was produced using 2DGE and MS [11]. It was suggested that small heat shock protein Hsp70-1B among 21 studied proteins, might serve as a biomarker of low tenderness in beef [12]. Other earlier studies suggested biomarkers such as myosin heavy chain isoforms or lactate dehydrogenase chain B seemed to be muscle-or breed-specific.…”
Section: Proteomics In Research On Muscle Biochemistrymentioning
confidence: 99%